2012
DOI: 10.1371/journal.pone.0032866
|View full text |Cite
|
Sign up to set email alerts
|

Melt Analysis of Mismatch Amplification Mutation Assays (Melt-MAMA): A Functional Study of a Cost-Effective SNP Genotyping Assay in Bacterial Models

Abstract: Single nucleotide polymorphisms (SNPs) are abundant in genomes of all species and biologically informative markers extensively used across broad scientific disciplines. Newly identified SNP markers are publicly available at an ever-increasing rate due to advancements in sequencing technologies. Efficient, cost-effective SNP genotyping methods to screen sample populations are in great demand in well-equipped laboratories, but also in developing world situations. Dual Probe TaqMan assays are robust but can be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 40 publications
4
95
0
4
Order By: Relevance
“…Furthermore, we suspected this relationship might be stronger if we focused on the proportion of individuals that carried more than one resistance SNP. We We designed Melt-MAMA qPCR assays [38] for three SNP positions. Two assays distinguish susceptible versus resistance SNPs previously described in the exons for domain II C190A and domain III T2134A [25,27].…”
Section: Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, we suspected this relationship might be stronger if we focused on the proportion of individuals that carried more than one resistance SNP. We We designed Melt-MAMA qPCR assays [38] for three SNP positions. Two assays distinguish susceptible versus resistance SNPs previously described in the exons for domain II C190A and domain III T2134A [25,27].…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Real-time qPCR assays were developed for Rhipicephalus microplus based on the Melt-MAMA platform [38] to rapidly screen thousands of ticks for resistance SNPs at three loci in the para-sodium channel gene.…”
Section: Additional Filesmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on its simplicity, low cost, non-destructive nature, high sensitivity and specificity, the popularity of HRM analysis has grown considerably in the last few years. HRM analysis is an effective alternative to other [29]. HRM is an ideal format for scoring a small number of SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the strains were identified on species level with a dual-probe TaqMan assay targeting a single nucleotide polymorphism (SNP) in the plcR gene (Easterday et al, 2005). The genotypes of the isolates were determined with melt mismatch amplification mutation assays according to Birdsell et al (2012) targeting the SNPs identified by Van Ert et al (2007).…”
Section: Methodsmentioning
confidence: 99%